Multiple Linear Regression Analysis of Factors Influencing Human Development Index By Regency/City in East Java Province in 2024 - Nurul Itsnaini; Agung Prabowo; Diah Paramita Amitarwati (International Journal of Quantitative Research and Modeling, 2025)
The Human Development Index (HDI) is an indicator used to assess the success of human development. The Human Development Index (HDI) is used to measure the impact of efforts to improve basic human capital capabilities. Based on BPS data, the HDI in East Java has consistently increased and has reached a high category, however, when compared to DKI Jakarta and DI Yogyakarta, the HDI in East Java is still relatively low. This study aims to determine the factors that influence the HDI in East Java Province. The research data are the 2024 HDI data for East Java Province obtained from the BPS of Lamongan Regency and the BPS website of East Java Province. This study uses the multiple linear regression method with RStudio software. Based on the results of the study, the multiple linear regression model with HLS, RLS, UHH, and GK factors has an influence of 97.94% on the HDI in East Java Province, while the TPT does not show a significant influence on the HDI in East Java Province.